Menskala naik satu proses fermentasi berdasarkan pekali pemindahan isipadu (kLa)oksigen tetap - Ahmad Jaril Asis; Zulaikha Paidi; A. Winkler, Michael; Jailani Salihon (1990)

(untitled)
The production of the enzyme cytochrome P-450 by Saccharomyces cerevisiae N.C.Y.C. 754 in batch fermentations using a coconut water based medium was scaled-up from shake flask to a 2-liter stirred - tank fermenter scale using the method of constant volumetric transfer coefficient (kLa) of oxygen.. kLa values were derived by fitting the mass transfer equation to the data of dissolved oxygen tension (DOT) versus time on computer using the Simplex Method with two unknowns, namely kLa and the electrode mass transfer coefficient (kap) of oxygen. The stirrer speed (RPM) and the air flowrate, (A) in the 2-liter fermenter that produced the value of kLa found in the optimised conditions in shake flask was approximated by trial and error. A fermentation run in the 2-liter fermenter using these values of RPM and A gave an enzyme yield comparable to that achieved in shake-flasks